第61次日本南極地域観測隊における「しらせ」を活用した採泥調査 - 板木, 拓也; Itaki, Takuya; 徳田, 悠希; Tokuda, Yuki; 石輪, 健樹; Ishiwa,Takeshige; 佐々木, 聡史; Sasaki, Satoshi; 菅沼, 悠介; Suganuma, Yusuke; 青木, 茂; Aoki, Shigeru (情報・システム研究機構 国立極地研究所, 2024)
第61次日本南極地域観測隊（JARE-61）では，南極観測船「しらせ」（AGB-5003）による初の本格的な採泥観測が行われた．堆積物試料は，大口径グラビティーコアラー及びGSJ型木下式グラブ採泥器を用い，トッテン氷河前縁～ダルトン・ポリニア海域，リュツォ・ホルム湾，ケープダンレー・ポリニアの3海域の計28地点において採取された．本論では，今後の調査の参考としてオペレーションの詳細を記録するとともに，これらの試料を用いた今後の分析の基礎情報として，得られた堆積物の予察観察結果を報告する． The first systematic sediment survey by the icebreaker Shirase (AGB-5003) was conducted during the 61st Japanese Antarctic Research Expedition (JARE-61). Sediment samples were obtained from a total of 28 sites in 3 areas of the Totten Glacier front–Dalton polynya, Lützow-Holm Bay and Cape Darnley polynya using a large-bore gravity corer and GSJ-type K-grab sampler. In this paper, details of the survey operation are described as a reference for the future experience. In addition, preliminary results of the obtained sediments are reported as a fundamental information for future analysis using these samples. departmental bulletin paper